2007
DOI: 10.1037/0893-164x.21.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Comparing gain- and loss-framed messages for smoking cessation with sustained-release bupropion: A randomized controlled trial.

Abstract: Prospect theory suggests that because smoking cessation is a prevention behavior with a fairly certain outcome, gain-framed messages will be more persuasive than loss-framed messages when attempting to encourage smoking cessation. To test this hypothesis, the authors randomly assigned participants (N = 258) in a clinical trial to either a gain-or loss-framed condition, in which they received factually equivalent video and printed messages encouraging smoking cessation that emphasized either the benefits of qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 48 publications
5
132
2
4
Order By: Relevance
“…Because smoking cessation prevents cancer and other health problems, several studies ( 25 -28 ) have examined the effect of gain-framed messaging on various smoking behaviors, and all have obtained encouraging results. Toll et al ( 25 ) showed that participants who completed a 7-week course of open-label bupropion SR (a smoking cessation pharmacotherapy) and received gain-framed messages, compared with loss-framed messages, achieved statistically signifi cantly…”
Section: Methodsmentioning
confidence: 99%
“…Because smoking cessation prevents cancer and other health problems, several studies ( 25 -28 ) have examined the effect of gain-framed messaging on various smoking behaviors, and all have obtained encouraging results. Toll et al ( 25 ) showed that participants who completed a 7-week course of open-label bupropion SR (a smoking cessation pharmacotherapy) and received gain-framed messages, compared with loss-framed messages, achieved statistically signifi cantly…”
Section: Methodsmentioning
confidence: 99%
“…The findings of this study suggest a need to shift focus once people try to enact a new lifestyle choice to focus on maximizing the immediate benefits they obtain from it, or maintaining the promise that these benefits will occur in time, rather than continuing to focus on the things that motivated the change in the first place. Gain-framed communications might be more important once a person has actually quit than when they are only contemplating trying (Toll et al, 2007). Strong disease-related messages are potent motivators of making quit attempts (National Cancer Institute, 2008) but may play little role in maintenance.…”
Section: Core Predictor Variablementioning
confidence: 99%
“…The "Prospect Theory" approach (successful in smoking research) 40 was recommended, promoting the gain from performing an action such as improved vision and comfort from replacing lenses when scheduled (gain-framed) rather than advising that they might experience poor vision discomfort if the patient is noncompliant (loss-framed). While compliance improving strategies have been much discussed, these have either not been tested 41,42 or not been successful, such as the implementation of a regular review exercise, 43 combining written and oral instructions 27 although this can improve case cleaning compliance 39 and intense instruction and reduced cost care products, although re-instruction enhances , 44,45 probably as anxiety is highest during communication interaction which will reduce information retention.…”
Section: Failure To Replace Lenses When Scheduledmentioning
confidence: 99%